1983
DOI: 10.1007/bf03186188
|View full text |Cite
|
Sign up to set email alerts
|

Histology and histochemistry of the tegumental glands inLigia exotica Roux (Crustacea:Isopoda)

Abstract: The tegumental glands in Ligia exotica are located around the oesophagus and also in the tissues of maxillae and maxillipeds. Each gland consists of a number of acini and each acinus is made of a rosette of 8-11 large conical cells. Histochemical observations of these glands reveal the presence of strongly sulphated and carboxylated acid mucopolysaccharides and neutral mucopolysaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They believed that muscular contraction discharged mucus into the oesophagus which then acted as a lubricant to facilitate the passage of food. Kumari et al (1983) used a range of histochemical tests in their study of oesophageal glands in the isopod Ligia exotica Roux. They found that the gland secretions were mostly sulphated and carboxylated mucopolysaccharides and suggested that in addition to assisting food swallowing, the acid nature of the secretions could indicate a role in predigestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They believed that muscular contraction discharged mucus into the oesophagus which then acted as a lubricant to facilitate the passage of food. Kumari et al (1983) used a range of histochemical tests in their study of oesophageal glands in the isopod Ligia exotica Roux. They found that the gland secretions were mostly sulphated and carboxylated mucopolysaccharides and suggested that in addition to assisting food swallowing, the acid nature of the secretions could indicate a role in predigestion.…”
Section: Discussionmentioning
confidence: 99%
“…He stated that a salivary gland function for land isopods was improbable and the glands may be concerned with cuticle formation. Histochemical analyses by various workers have indicated that acid and neutral mucopolysaccharides are secreted which may aid in food ingestion and digestion in harpacticoid copopods (Gharagozlou-van Ginneken, 1977), isopods (Kumari et al, 1983), amphipods (Shyamasundari, 1979) and alpheids (Rajendranath et al, 1984). Support for a salivary gland function has been provided by Elofsson et al (1978) who identified a mixture of d opamine or catechol compounds using microspectrofluorimetric analysis in gammarid amphipods.…”
Section: Introductionmentioning
confidence: 99%